Sparsentan: Sparsentan- A novel, non- immunosuppressive, dual action angiotensin II and endothelin A receptor antagonist -A new hope for glomerular disease (Journal of Shaheed Suhrawardy Medical College, 2024)
Abstract not availableJ Shaheed Suhrawardy Med Coll 2022; 14(2): 58-62